Contesting Ethnoarchaeologies
VIII, 256 p. 48 illus., 12 illus. in color.
Keywords: Contesting Ethnoarchaeologies provide a systematic overview of major non-American traditions of ethnoarchaeology, with a particular focus on Europe and Asia. It explores all stages of their research agenda. These ethnoarchaeologies were embedded in theoretical traditions of local archaeologies. Moreover, ethnoarchaeological studies carried out in these different settings targeted a wide range of different issues and addressed numerous questions of covering all sorts of different issues. Consequently, achieved results and data have been largely idiosyncratic and hardly compatible. Hence, this volume aims not only to conceptualize characteristics of these diverse ethnoarchaeologies but more importantly put them in a broader context of the development of archaeology in different parts of Europe and Asia. The contributors to the volume express their own diverse views on the cognitive and interpretative value of ethnoarchaeology for studying prehistoric past, based on particular cases of experience and research. As such, the volume is not only a valuable overview of numerous ethnoarcheological practices in different parts of the region, but also a significant contribution to the history of archaeological thought. This perspective shall make the book of wider applicability and make possible to put up ethnoarchaeology as an immanent and important element of archaeological theory. .